PENGEMBANGAN TES DIAGNOSTIK KESULITAN BELAJAR MATEMATIKA DI SD - Duskri, M.; Kumaidi, Kumaidi; Suryanto, Suryanto (Jurnal Penelitian dan Evaluasi Pendidikan, 2014)
Tujuan penelitian untuk: (1) menemukan prosedur pengembangan tes diagnostik kesulitan belajar matematika SD/MI, (2) mengetahui kualitas butir tes diagnostik yang dikembangkan, dan (3) mengetahui informasi yang dapat dimunculkan dari hasil analisis tes diagnostik. Penelitian ini merupakan penelitian pengembangan dari Borg & Gall. Subjek uji sebanyak 542 orang siswa kelas VI SD/MI di Kota Banda Aceh dan Aceh Besar. Analisis kuantitatif untuk mengetahui informasi butir tes menggunakan program ITEMAN dan Program R. Hasil penelitian menunjukkan: (1) pengembangan tes diagnostik kesulitan belajar matematika di SD ini meliputi: studi pendahuluan, studi literatur dan hasilhasil penelitian, analisis masalah, merumuskan learning continuum, merumuskan peta konsep, menyusun tes essay, polarisasi jawaban siswa, menyusun tes bentuk pilihan ganda, validasi pakar melalui focus group discussion, uji coba terbatas, dan uji yang diperluas, (2) indeks daya beda butir tes antara 0,391 sampai dengan 2,317, indeks kesukaran butir tes antara -2,158 sampai dengan 2,528, kecocokan uji tes dengan kemampuan peserta (Î¸) antara -2,00 sampai dengan 2,60, dan fungsi informasi tes antara 0,111 sampai dengan 3,879, dan (3) informasi yang dapat dimunculkan dari tes meliputi: hasil tes secara klasikal dan individual, grafik ketuntasan belajar, profil individual, analisis salah konsepsi dan saran remedial.Kata kunci: tes diagnostik, kesulitan belajar matematika______________________________________________________________DEVELOPING DIAGNOSTIC TEST OF MATHEMATICS LEARNING DIFFICULTIES IN ELEMENTARY SCHOOLSAbstract The purposes of this study were: (1)to find a method to develop diagnostic test of mathematics learning difficulties in primary schools, (2) to determine the diagnostic test characteristics developed, and (3) to determine the information that could be generated by using diagnostic test. This study was a development research by Borg & Gall. The participants of main field testing were 542 grade VI students of primary schools in Banda Aceh City and Aceh Besar Regency. The quantitative analysis to determine the information of the test items developed used ITEMAN program and R Program. The results of this study are: (1) in developing the diagnostic test of the mathematics learning difficulties, the research phase included preliminary study, literature and research results study, problem analysis, formulating learning continuum, formulating concept map, preparing essay-form tests, students' answers polarization, preparing multiple-choice tests, experts' validation with focus group discussion, preliminary and readability tests, operational field testing, and main field testing to obtain model that fitted theoretically and empirically, (2) discriminating power of test items index ranges from 0.391 to 2.317, the difficulty test items index ranges from -2.158 to 2.528, the test compatibility testing with the participants ability (0) ranges from -2.00 to 2.60 and the test information function ranges from 0.111 to 3.879, and (3) the information that can be generated from the diagnostic test includes classically and individually test results, graphic of learning outcomes attainment, individual profile, every answers analysis, false conception and remedial suggestion analysis.Keywords: diagnostic test, mathematics learning difficulties